ENHANCING PUBLIC SPEAKING TO ENGLISH FOR YOUNG LEARNERS VIA EXTEMPORANEOUS SPEECH: A COMPREHENSIVE APPROACH USING SPEAKING EVALUATION CRITERIA - Defy Gustianing; Arif Alexander Bastian; Eka Pratiwi Yunianti; Aji Sugiharto, Prasetyawan (Universitas Aisyah Pringsewu, 2024)
This study explores the enhancement of public speaking skills in English for young learners through the implementation of extemporaneous speech techniques, utilizing a comprehensive approach guided by speaking evaluation criteria. Extemporaneous speech, which requires speakers to deliver presentations with minimal preparation, fosters critical thinking, quick organization, and engaging delivery skills essential for effective public speaking. By employing the Oxford Evaluation Criteria, which assesses key components such as the oral introduction, body of speech, summary, attire, performance, audience engagement, creativity, and use of sources, this study provides a structured framework for evaluating and improving these abilities. The research compares the performance of a control group using traditional speaking methods with an experiment group practicing extemporaneous speech. Results indicate that the experiment group shows significantly higher achievement, demonstrating enhanced fluency, coherence, audience engagement, and creativity. These findings suggest that integrating extemporaneous speaking into language learning programs can substantially improve young learners' public speaking proficiency, making it a valuable approach in educational settings.